Exploring the interplay of coach behaviours, team resilience, support perception, and collective efficacy in young team athletes - Adilogullari, I.; Senel, E.; Kerr-Cumbo, R.; Aydemir, R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Team sports create a social-psychological environment that shapes athletes` responses to pressure and challenges. Belief in the team`s ability to cope with demanding conditions is crucial for individual motivation and collective success, strengthening performance, social bonds, and psychological resilience. This study examines the relationships between perceived supportive coach behaviours, team resilience, and collective efficacy in young athletes. A total of 285 athletes from football, basketball, volleyball, and handball participated, with validated instruments used to measure coach behaviours, team resilience, perceived support, and collective efficacy. Structural Equation Modelling (SEM) assessed the interrelationships among these variables. Findings showed that perceived support significantly influences athletes` recognition of supportive coach behaviours, enhances resilience, and reduces vulnerability under pressure. Collective efficacy was a key predictor of resilience and negatively correlated with vulnerabilities. Supportive coaching behaviours alleviated stress and promoted resilience, highlighting the importance of a positive team environment. Indirect effects indicated that perceived support enhances resilience through collective efficacy and supportive behaviours, underlining their mediating role in strengthening team dynamics and psychological responses. The study underscores the importance of perceived support and supportive coaching in fostering resilience and collective efficacy. Athletes who feel supported are more likely to demonstrate resilience and cope with challenges effectively. Coaches should prioritise supportive environments that encourage positive relationships and resilience, helping athletes manage stress and improve performance. Future research could explore the long-term impact of these factors across different team sports.